Facilitating Informal Workplace Learning for Organizational Capacity and Public Service Improvement: Managers' Experiences in Cambodia's Sub-National Administrations - Sour Sokh; Bunhe Harth; Thearom Ret (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the Study: This study explores how managers facilitate informal workplace learning within Cambodia’s sub-national administrations. It examines the managerial practices, workplace conditions, and organizational factors that support employee learning and development and contribute to organizational capacity within decentralized public-sector organizations. Methodology: A qualitative exploratory design was employed to examine managers’ experiences of facilitating informal workplace learning within Cambodia’s sub-national administrations. Data were collected through 14 semi-structured interviews involving 16 managerial participants, including governors, deputy governors, administrative directors, deputy administrative directors, and office chiefs across multiple levels of sub-national administration. Interviews were conducted in Khmer, transcribed, translated into English, and analyzed using reflexive thematic analysis. Main Findings: Four interrelated dimensions of managerial facilitation of informal workplace learning were identified: structuring opportunities for learning, creating supportive learning climates, developing employee capability through work participation, and managing organizational constraints affecting learning. The findings demonstrate that managers play a central role in creating learning-supportive workplace environments that foster employee development and strengthen organizational capacity within Cambodia’s sub-national administrations. Novelty/Originality of this Study: This study provides an empirically grounded framework of managerial facilitation of informal workplace learning within a decentralized public-sector context. It advances workplace learning research by introducing Constraint-Adaptive Learning Facilitation as an emerging conceptual proposition and demonstrates how workplace learning can strengthen employee capability, organizational capacity, and public service effectiveness.